Germination of clove seeds: effect of temperature, fruit pulp and fungicide treatment - Maeda, Jocely Andreuccetti; Bovi, Marilene Leão Alves; Bovi, Odair Alves; do Lago, Antonio Augusto (Pesquisa Agropecuaria Brasileira, 1991)
The effects of temperature, pulp removal and fungicide on the germination, emergence and seedling growth of clove tree (Syzygium aromaticum (L.) Merr. et Perry) seeds, were studied under laboratory and nursery conditions. Alternated temperature of 20 to 30°C (16 hours at 20°C and 8 hours at 30°C) increased germination percentage as well as speed of germination, as compared to constant temperatures (20, 25 and 30°C). Pulp removal increases germination, emergence and speed index. Seedlings from pulp removed seeds were 20.88% taller than unpeeled seeds. Fungicide treatment increased germination of pulp removed seeds under laboratory conditions. No significative fungicide effects were observed under nursery conditions.